Lifetime Test of Tracked Vehicle Torsion Bars using Monte Carlo Method - Jan Furch; Quy Hung Nguyen (Ital Publication, 2020)
The article deals with the service life of torsion bars in tracked vehicles. The aim of the article is to show the suitability of accelerated tests and modelling for determining the service life of torsion bars, which takes many years in real operation. The design of a test bench for accelerated tests is presented together with limiting conditions, which were afterwards verified. Subsequently, a virtual model of the torsion bar of a tracked vehicle was created with the help of finite elements. Dynamic modelling was performed by MSC Adams software with a module using finite elements. Furthermore, the article shows the possibility of using the Monte Carlo method to determine the service life of torsion bars of tracked vehicles. The Monte Carlo utility of Accelerated Life Testing Analysis (ALTA) software is used to obtain failure data at specified test stress levels. Using the Monte Carlo simulation, one data set is generated containing values that are arranged in dependence on the specific lifetime distribution of the Weibull distribution. Finally, a comparison of the experiment with the calculated values is performed. The results obtained can be used to compile an accelerated test plan. This modelling design saves a lot of money and time to determine the life of the torsion bar in tracked vehicles.